An Exploratory Survey Measuring Stigma and Discrimination Experienced By People Living With HIV/AIDS - Makadia, Khushbu D; Patel, Parimal R (National Journal of Community Medicine, 2018)
Background: The continued presence of stigma makes it an ex- traordinarily important, yet difficult issue to eradicate. The study aimed to assess HIV/AIDS related stigma and discrimination trends experienced by people living with HIV/AIDS (PLHA). Methodology: The cross sectional study was conducted in ICTC and STI clinic among 378 PLHA. Convenience sampling method was used as the study was limited to only participants who had voluntarily disclosed their HIV status could be involved for ethical reason. Consent was taken. A pre-tested questionnaire was used. Result: Findings suggest that PLHA have experienced significant levels of stigma and discrimination. Internalized stigma was among 89% of the participants and they blamed themselves for their status. While 86% respondents facing discriminatory atti- tudes from the society. Stigma and discrimination observed more in female and it was statistically significant. Conclusion: The current measures for dealing with stigma should be expanded to incorporate the issues related to health, education and discrimination experienced in various places. Family, Peer and Individual counseling should be an essential component for care of PLHA.